Biomarcadores da carcinogênese no diagnóstico anatomopatológico diferencial de neoplasias malignas biliopancreáticas - Jordão, Pedro Henrique Fogaça (2024)
Introduction – Pancreatic ductal adenocarcinoma (ACDP) and cholangiocarcinoma (CCA), classified as extrahepatic (eCCA) and intrahepatic (iCCA), are biliopancreatic malignant neoplasms, posing a challenge in differential diagnosis due to their anatomopathological similarities. Objectives – To analyze gene and protein expression of the carcinogenesis pathways PIK3CA/PTEN, SMAD4/TGF-β1, and VEGF-A/VEGF-R2/HIF-1α in CCA and ACDP, and their association with anatomopathological characteristics, aiming to identify markers for differential diagnosis. Casuistry and Methods – A total of 67 individuals were studied: 22 patients with ACDP, 17 with eCCA, and 13 with iCCA; and controls without neoplasms: seven samples of biliary duct tissue (BDNN) and eight of pancreatic duct tissue (PDNN). For gene (RT-qPCR) and protein (immunohistochemistry/ImageJ/HistoScore) expression analysis, fresh or paraffin-embedded tissue samples were used. A significant value was considered for P<0.05. Results – There was a similarity in sex and age among patients, but they showed a higher age range compared to controls (P<0.05). Stage I/II prevailed in ACDP and III/IV in CCA, with lymphatic invasion in ACDP (P<0.05). Moderately differentiated tumors predominated in all groups. Gene overexpression of PIK3CA, PTEN, SMAD4, TGFB1, VEGFA, and KDR was observed in patients versus controls (P<0.02), while HIF1A was overexpressed only in iCCA (P=0.006). However, similarity was observed among patients, except for TGFB1, which was increased in iCCA versus ACDP and eCCA, as well as VEGFA and KDR in iCCA versus ACDP (P<0.05). Protein marking of p110α and PTEN showed cytoplasmic predominance in all tumor groups. On the other hand, SMAD4 was negative in most groups, although eCCA showed predominance for cytoplasmic marking. Additionally, TGF-β1 protein expression was notably more pronounced in ACDP than in other cancer types. VEGF-A, VEGF-R2, and HIF-1α exhibited variable marking patterns among groups, with HIF-1α negativity highlighted in iCCA. Protein expression was similar among groups; however, there was a difference (P<0.05) in gene and protein expression for: poorly differentiated cells (HIF1A and TGFB1: iCCA > ACDP) and moderately differentiated cells (KDR and TGFB1: iCCA > ACDP); vascular, lymphatic, and perineural invasion (TGFB1: iCCA > ACDP); perineural (TGF-β1: ACDP > eCCA); metastasis (TGF-β1: ACDP > iCCA), and stage III/IV (VEGFA, TGFB1, KDR: iCCA > ACDP; TGFB1: iCCA > eCCA; VEGF-R2: ACDP > eCCA). A moderate positive correlation (P<0.05) was observed between PIK3CA and PTEN in eCCA and iCCA; SMAD4 and TGFB1 in ACDP and iCCA; and VEGFA and HIF1A in ACDP and eCCA, and strong in iCCA. Discriminatory analysis revealed that TGFB1 gene expression had the best performance in differentiating iCCA from ACDP. For classification between iCCA and eCCA, TGFB1 and VEGFA were the best indicators. TGF-β1 and SMAD4 protein expression was clinically relevant for differentiating eCCA from ACDP. Conclusions – The differential gene and protein expression of these biomarkers is associated with the anatomopathological characteristics in biliopancreatic malignant neoplasms. SMAD4 and TGF-β1 protein expression shows potential for discriminating and classifying these diseases.